O “Natal dos Paraenses”: a alimentação de Belém no Círio de Nazaré (1930-1950) - SANTOS, Arthur Camarão dos (2024)
During the month of October, in the city of Belém (PA), Brazil's largest Catholic event takes place: the Círio de Nazaré. This event is accompanied by a diversity of food and identity specific to this time of year, with typical dishes that convey a sense of belonging. Based on this understanding, this study aims to explore the food culture of Belém during the Feast of Our Lady of Nazaré in the 1930s, 1940s and 1950. The goal is to identify which foods were considered festive in that society, whit a focus on regional dishes.